Nutritional quality and health benefits of microgreens, a crop of modern agriculture - Yanqi Zhang; Zhenlei Xiao; Emily Ager; Lingyan Kong; Libo Tan (Journal of Future Foods, 2021)
Microgreens are young, tender greens that are used to enhance the color, texture, or flavor of salads and main dishes. They can be grown in small scales and indoors, making them widely adopted by controlled environment agriculture, an indoor farming practice is particularly important for feeding increasing urban populations. Besides, microgreens are attracting more consumers’ attention due to their high nutritional value and unique sensory characteristics. This review focuses on the nutrition quality, sensory evaluation, pre- and post-harvest interventions, and health benefits of microgreens. Microgreens are rich in vitamins (e.g., vitamin C), minerals (e.g., copper and zinc), and phytochemicals, including carotenoids and phenolic compounds, which act as antioxidants in human body. Pre-harvest interventions, such as illumination, salinity stress, nutrient fortification, and natural substrates, influence the photosynthetic and metabolic activities of microgreens and were shown to improve their nutritional quality, while the effects varied among species. After harvesting, packaging method and storage temperature can influence the nutrient retention in microgreens. Both in vitro and in vivo studies have shown that microgreens have anti-inflammatory, anti-cancer, anti-bacterial, and anti-hyperglycemia properties, making it a new functional food beneficial to human health. The sensory attributes and overall acceptability and liking of microgreens are primarily influenced by their phytochemical content. Microgreens are only getting popular during the last decades and research on microgreens is still at its early stage. More studies are warranted to optimize the pre- and post-harvest practices for nutrient enhancement and retention and to explore the potential health benefits of different microgreens for the prevention and treatment of chronic diseases.